Динамические характеристики линейных объектов с переменными параметрами - Протасов, С.Ю. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2010)
In this article the basic types of integral dependence are analyzed between a weekend and by an entrance the signals of linear dynamic objects with in-out parameters.